Q. 85.0( 2 Votes )

Let f: R →<

Answer :

Let f: R R and g: R R are defined as


f (x) = x + 1 and g (x) = x – 1


Now,


fog(x) = f(g(x)) = f(x – 1) = x – 1 + 1


= x =IR ……(i)


Again,


fog(x ) = f(g(x)) = g(x + 1) = x + 1 – 1


= x = IR ……(ii)


from (i)& (ii)


fog = gof = IR


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar